If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -2x = 6x + -10x + 2 Reorder the terms: 6 + -2x = 2 + 6x + -10x Combine like terms: 6x + -10x = -4x 6 + -2x = 2 + -4x Solving 6 + -2x = 2 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 6 + -2x + 4x = 2 + -4x + 4x Combine like terms: -2x + 4x = 2x 6 + 2x = 2 + -4x + 4x Combine like terms: -4x + 4x = 0 6 + 2x = 2 + 0 6 + 2x = 2 Add '-6' to each side of the equation. 6 + -6 + 2x = 2 + -6 Combine like terms: 6 + -6 = 0 0 + 2x = 2 + -6 2x = 2 + -6 Combine like terms: 2 + -6 = -4 2x = -4 Divide each side by '2'. x = -2 Simplifying x = -2
| 23=-7u+(u-3) | | (y+4)(y-7)=0 | | 1n+3=4n-12 | | 3*a^2+28*a+49=0 | | (3x+24)=42 | | 18=3m-3m | | (4u+3)(2-u)=0 | | 3x=(-6) | | (w+4)(w+1)=0 | | 8-3y=22 | | 3*b^2+b-2=0 | | 5+2(n+1)=-18 | | 3x+20=10x-36 | | X-2=(-2) | | 310x-278=722-190x | | 2(n-5)=4 | | 153+z^2=378 | | u^2+2u+1=0 | | 3x^2-1=47 | | v^2+11*v+19=-5 | | 14.0=8.6+0.9m | | 6w+5=8w+11 | | 6(3x-8)=3(6x+1) | | 0=32t-16t^2 | | k^2-1=3 | | 220=2(2w-40)+2w | | 6+18z-1=6z+47-2z | | 8(8b+7)+8(b-4)=24 | | x-.1x=72 | | 6x+9=2x+81 | | 2(5p+8)-3(p+7)=0 | | 2(3a+7)=26 |